A single-institutional review of 68 patients with dermatofibrosarcoma protuberans: wide re-excision after inadequate previous surgery results in a high rate of local control. Issue 1 (December 2017) - Harati, Kamran; Lange, Kim; Goertz, Ole; Lahmer, Armin; Kapalschinski, Nicolai; Stricker, Ingo; Lehnhardt, Marcus; Daigeler, Adrien
Abstract Background Dermatofibrosarcoma protuberans (DFSP) is a cutaneous soft tissue sarcoma characterized by an indolent but aggressive local growth. Unplanned excisions with positive margins are common, and the prognostic impact of radical re-excisions is still unclear. The aim of the present study was to identify prognostic indicators of recurrence-free survival (RFS) in patients with DFSP through a long-term follow-up. We tried particularly to determine the prognostic impact of surgical margins and re-excisions in patients after earlier inadequate surgery. Methods Seventy-five patients with DFSP were treated surgically at our institution between 1999 and 2015. Analyses were restricted to 68 participants with available information on surgical margins. The median follow-up was 5.4 years. Results Fifty-four patients (79.4%) had low-grade DFSP and 14 patients (20.6%) intermediate-grade FS-DFSP. The 5-year RFS rates were estimated to be 93.5% (95% CI 81.2–97.9) for low-grade DFSP and 39.7% (95% CI 13.0–65.8) for FS-DFSP (P  < 0.0001). Re-excisions were performed in 55 patients (80.9%) following R1 or marginal R0 resections. Negative margins could be attained in a total of 65 patients (95.6%). Negative margin widths >1 cm led to the best local outcome within the R0 subgroup. Significant adverse prognostic features in the multivariate analysis included histologic grade and close margins. Conclusions The data from this study underscore the long-term benefit of negative margins. In our analysis, re-excisions were an effective method to achieve a high rate of local control in patients who presented after R1 or marginal R0 resection. To ensure the best outcome, re-excisions should aim at negative margin widths of more than 1 cm in the histologic specimen.